Ergonomic Design of a Paving Block Transport Tool Using Anthropometry and Design Thinking Approaches - Bagus Rachman Saputra; Iftitah Ruwana; Sanny Andjar Sari (JTI: Jurnal Teknik Industri, 2025)
This study aims to design an ergonomic paving block transport tool using an anthropometric and design thinking approach to reduce musculoskeletal risk among workers. The research began by assessing worker postures through the Rapid Entire Body Assessment (REBA) method and measuring relevant anthropometric dimensions to inform the tool’s ergonomic specifications. The design process applied a human-centred design thinking framework, incorporating user needs and physical data. REBA analysis showed that Worker 1 had a score of 8 (high risk, requiring immediate intervention), while Worker 2 had a score of 5 (moderate risk). The recommended lifting index was calculated at 0.71, indicating an acceptable workload. Anthropometric data determined key design parameters, including tool height (136 cm), grip height (94 cm), tool width (68 cm), and reach length (73 cm), based on the 5th and 50th percentiles of worker measurements. The selected tool design utilized steel materials for strength and durability and incorporated a rack and lifting mechanism to accommodate up to five paving block boards per transfer. Field testing demonstrated a 257% increase in production capacity and a 33% reduction in transport time. The tool design successfully addressed key ergonomic risks, enhanced operational efficiency, and supported safer manual material handling practices. The study concludes that combining anthropometric data with design thinking can lead to effective ergonomic interventions in construction environments.Keywords: REBA, ergonomics, anthropometry, design thinking, lifting trolley, manual material handling